To analyze the expression \( 6 - \frac{1}{4} \cdot 28 - 2 \) and compare it to \( \frac{3}{4} + 4 \cdot 2 - 11 \), let's calculate both sides step by step.
Left side:
- \( 6 - \frac{1}{4} \cdot 28 - 2 \)
- Calculate \( \frac{1}{4} \cdot 28 = 7 \)
- Now substitute that back into the expression: \( 6 - 7 - 2 \)
- Perform the operations: \( 6 - 7 = -1 \), then \( -1 - 2 = -3 \)
So, the left side equals \( -3 \).
Right side:
- \( \frac{3}{4} + 4 \cdot 2 - 11 \)
- First calculate \( 4 \cdot 2 = 8 \)
- Substitute that into the expression: \( \frac{3}{4} + 8 - 11 \)
- Next, perform the addition and subtraction: \( 8 - 11 = -3 \), then \( -3 + \frac{3}{4} = -3 + 0.75 = -2.25 \)
So, the right side equals \( -2.25 \).
Now we can compare:
- Left side: \( -3 \)
- Right side: \( -2.25 \)
Now, we need to insert an operator. Comparing -3 and -2.25, we see that:
\(-3 < -2.25\)
Therefore, the correct operator to insert is \( < \).
Final answer: \( < \)